(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Smart materials, with their unique ability to respond dynamically to external stimuli, have emerged as a transformative force in the field of mechanical engineering. This comprehensive review paper delves into the world of smart materials and structures, shedding light on their properties, applications, challenges, recent developments, and future prospects. The paper begins with an exploration of various types of smart materials, including piezoelectric materials, shape memory alloys, magnetostrictive materials, electrostrictive materials, and phase-change materials. Each material’s distinctive properties and characteristics are examined in depth, followed by a discussion of their wide-ranging applications within the mechanical engineering domain. From structural health monitoring to vibration control, adaptive structures, and energy harvesting, smart materials have revolutionized the way mechanical systems operate. They offer innovative solutions to age-old engineering challenges, promising enhanced efficiency, safety, and sustainability. However, this transformative potential is not without its hurdles. Reliability and durability issues, cost considerations, integration complexities, and environmental concerns must be addressed to fully harness the benefits of smart materials. Despite these challenges, the field of smart materials is marked by continuous innovation and promising breakthroughs. Recent advancements in nanotechnology and the emergence of multifunctional smart materials are reshaping the landscape of mechanical engineering. These materials find applications in emerging industries such as healthcare and automotive, highlighting their growing significance in contemporary engineering solutions.